Cervical intraepithelial neoplasia and cervical cancer in Hunan Province, China, 2020-2023 - Zhou, Xu; Han, Ting; Guo, Tingting; Liu, Yaqin; Li, Hongyun; Yingxia, Wang; Wu, Yinglan (Frontiers in Oncology, 2024)
ObjectiveTo describe the incidence and distribution of cervical intraepithelial neoplasia (CIN) and cervical cancer (CC) for rural women aged 35-64 in Hunan Province, China, 2020-2023.MethodsData were from the Hunan Provincial Cervical Cancer Screening Program in Rural Areas. Most rural women aged 35-64 in Hunan Province attend the program. All women diagnosed with CINs and CCs will be asked to register detailed information, including pelvic examination, diagnosis, age, education level, etc. CINs included low-grade squamous intraepithelial lesions (LSIL) (CIN1), high-grade squamous intraepithelial lesions (HSIL) (CIN2 and 3); CCs included adenocarcinoma in situ (AIS), early invasive cervical cancer (EICC) (stage Ia1 and Ia2) and invasive cervical cancer (ICC) (stage Ib and above). The incidence of CIN and CC is the number of cases per 1000 women. Chi-square tests (χ2) were used to examine if there were significant differences in proportions among different groups.ResultsA total of 4150700 women were included, and 67071 CINs and CCs were identified. The incidence of LSIL, HSIL, AIS, EICC and ICC were 10.63‰(95%CI: 10.53-10.73), 4.98‰(95%CI: 4.91-5.05), 0.06‰(95%CI: 0.06-0.07), 0.23‰(95%CI: 0.22-0.25), and 0.26‰(95%CI: 0.24-0.27), respectively. The proportion of previous pelvic examinations was relatively low in EICC (17.24%) and ICC (17.45%) (χ2 = 236.57, P <0.01), present abnormal examination was relatively high in AIS (51.33%), EICC (49.74%) and ICC (62.45%) (χ2 = 331.15, P <0.01). HPV16 was the most common high-risk type for LSIL (22.01%), HSIL (36.92%), AIS (46.01%), EICC (58.88%), and ICC (64.34%). The proportion of HSIL was relatively high in women aged 35-44 (27.03%), AIS was relatively high in women aged 45-54 (46.39%), EICC (44.24%), and ICC (48.58%) was relatively high in women aged 55-64. The proportion of ICC was relatively high in women with elementary school (38.68%), HSIL (15.10%) and AIS (17.49%) was relatively high in women with senior high school, AIS (1.52%), EICC (0.62%) and ICC (0.75%) was relatively low in women with university and above. (P <0.01).ConclusionWe have described the incidence and distribution of CIN and CC among rural women aged 35-64. These findings were clinically relevant and were useful for clinical counseling and early diagnosis of CC.